1993
DOI: 10.1111/j.1469-8137.1993.tb03932.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of cadmium on non‐mycorrhizal and mycorrhizal Norway spruce seedlings [Picea abies (L.) Karst.] and its ectomycorrhizal fungus Laccaria laccata (Scop, ex Fr.) Bk. & Br.: Sulphate reduction, thiols and distribution of the heavy metal

Abstract: SUMMARY The effect of cadmium on assimilatory sulphate reduction and thiol content was studied in non‐mycorrhizal and mycorrhizal Norway spruce seedlings (Picea abies) and its ectomycorrhtzal fungus Laccaria laccata. The distribution of cadmium was also investigated. Isotope dilution experiments indicated that the fungus reduced sulphate via adenosine 3′‐phosphate 5′‐phosphosulphate sulphotransferase, whereas Norway spruce seedlings assimilated sulphate via adenosine 5′‐phosphosulphate sulphotransferase in bot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
20
1
1

Year Published

1996
1996
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(24 citation statements)
references
References 38 publications
0
20
1
1
Order By: Relevance
“…This class of metallothioneins is now known to be widespread in fungi (Kneer et al, 1992). In a study of the effects of cadmium on Norway spruce seedlings infected with Laccaria laccata, phytochelatins were detected in mycorrhizal roots, but neither these, nor other metallothioneins, were present in the isolated fungus (Galli, Meier & Brunold, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…This class of metallothioneins is now known to be widespread in fungi (Kneer et al, 1992). In a study of the effects of cadmium on Norway spruce seedlings infected with Laccaria laccata, phytochelatins were detected in mycorrhizal roots, but neither these, nor other metallothioneins, were present in the isolated fungus (Galli, Meier & Brunold, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…Thiol compounds, including reduced glutathione (␥-glutamyl cysteinyl glycine), phytochelatins (PCs), and metallothioneins, are essential components of Cd detoxification pathways in various organisms (5)(6)(7)11). Thiol composition of ectomycorrhizal fungi has not been studied in detail, although P. involutus and Laccaria laccata accumulate glutathione when exposed to Cd (7,22).…”
mentioning
confidence: 99%
“…Thiol composition of ectomycorrhizal fungi has not been studied in detail, although P. involutus and Laccaria laccata accumulate glutathione when exposed to Cd (7,22). Reduced glutathione is the most abundant nonprotein thiol component of eukaryotic cells, acts as a free radical scavenger, and reacts with various oxidants to produce oxidized glutathione (17).…”
mentioning
confidence: 99%
“…Decreased uptake in plants exposed to toxic concentrations of metals may provide some protection against metal toxicity, but the degree of protection differs among fungal isolates, metal elements and experimental conditions (Galli et al 1994). At high levels of Cd exposure, arbuscular mycorrhizal (AM) fungal colonization reduced Cd uptake, whereas at lower levels of exposure or low Cd availability, AM either enhanced or reduced Cd uptake (Schüepp et al 1987;El-Kerbawy et al 1989;Galli et al 1993). A recent study with bean and maize plants showed a significant increase in Cd uptake by plants infected with an AM fungus, Glomus mosseae .…”
mentioning
confidence: 99%